1975
DOI: 10.1099/00222615-8-3-455
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Group-F Streptococci From Human Sources

Abstract: I N comparison with the vast literature concerning group-A streptococci, our knowledge of group-F streptococci is very meagre and there is little published work concerning them. This report documents a series of 22 strains isolated from children and puerperal women during about 4 years and discusses their significance in human disease. MATERIALS AND METHODSPrimary cultures were inoculated on horse-blood agar (BBL Columbia Base; Becton, Dickinson and Co., Canada, Ltd, Mississauga, Ontario) and incubated at 37°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2

Year Published

1976
1976
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
4
11
2
Order By: Relevance
“…Although isolated 'minute' strains of group F and G from the throat in 6-8 % of normal subjects and Hare (1935) stated that strains of group F occurred mainly in the nasopharynx, more recent work does not support their observations on the importance of this site. Haemolytic strains occurred in only 41 (0.6%) of an estimated 7000 throat swabs examined in the present study, and Wort (1975) reported an isolation rate of only 0 04 % of group F strains from similar material. Guthof (1956) was unable to demonstrate non-haemolytic Strep.…”
Section: Discussioncontrasting
confidence: 52%
“…Although isolated 'minute' strains of group F and G from the throat in 6-8 % of normal subjects and Hare (1935) stated that strains of group F occurred mainly in the nasopharynx, more recent work does not support their observations on the importance of this site. Haemolytic strains occurred in only 41 (0.6%) of an estimated 7000 throat swabs examined in the present study, and Wort (1975) reported an isolation rate of only 0 04 % of group F strains from similar material. Guthof (1956) was unable to demonstrate non-haemolytic Strep.…”
Section: Discussioncontrasting
confidence: 52%
“…Ottens and Winkler (1962) found many strains of S. milleri in the dental root-canal, and we found them often on the surface of the teeth and on sutures removed after dental operations (Phillips et al, 1976). The anatomical distribution of the lesions in our series suggests that the source of a considerable number of them was in the abdomen, a conclusion reached by Wort (1975) from a study of group-F infections. Studies of the distribution of S. milleri in the gut have not been made, but Rogers (1957) isolated group-F streptococci from 11 % of acutely inflamed appendices.…”
Section: Purulent Diseasessupporting
confidence: 57%
“…It often grows poorly or not at all in the absence of CO,; many of the strains submitted to us had initially been described as " micro-aerophilic " or " anaerobic " streptococci. Meningitis, peritonitis, pleural empyema and bacteriaemia caused by group-F streptococci (Rantz, 1942;Wheeler and Foley, 1943 ;Foley, 1947;Koepke, 1965;Wort, 1975) or by non-haemolytic, bacitracinresistant group-A streptococci (Bannatyne and Robson, 1974) have been described; these organisms are very likely to have been S. milleri.…”
Section: Purulent Diseasesmentioning
confidence: 99%
“…Cultures of the oral cavity (50), throat (8,47), feces (71,75), and vagina (80) have all yielded "S. milleri" strains. Poole and Wilson (62) noted that a majority of isolates from teeth were hemolytic, but fecal and vaginal strains tended to be nonhemolytic.…”
Section: Clinical Significance Of "S Milleri"mentioning
confidence: 99%